The Technology of Production and Treatment of Materials in the Electric Field; Applied Mechanics and Materials; Vol. 682 : Innovation Technology and Economics in Engineering - Rodzevich A. P. Aleksandr Pavlovich (Material Science, Machining Technologies and Equipments in Mechanical Engineering, 2014)
Title screen